ENERGETICS OF MULTICOMPONENT DIFFUSION IN MOLTEN CAO-AL2O3-SIO2 - Liang Y.; Davis A.M. (My University, 2002)
The energetics of multicomponent diffusion in molten CaO-Al2O3-SiO2 (CAS) were examined experimentally at 1440 to 1650°C and 0.5 to 2 GPa. Two melt compositions were investigated: a haplodacitic melt (25 wt.% CaO, 15% Al2O3, and 60% SiO2) and a haplobasaltic melt (35% CaO, 20% Al2O3, and 45% SiO2). Diffusion matrices were measured in a mass-fixed frame of reference with simple oxides as end-member components and Al2O3 as a dependent variable. Chemical diffusion in molten CAS shows clear evidence of diffusive coupling among the components. The diffusive flux of SiO2 is significantly enhanced whenever there is a large CaO gradient that is oriented in a direction opposite to the SiO2 gradient. This coupling effect is more pronounced in the haplodacitic melt and is likely to be significant in natural magmas of rhyolitic to andesitic compositions. The relative magnitude of coupled chemical diffusion is not very sensitive to changes in temperature and pressure.To a good approximation, the measured diffusion matrices follow well-defined Arrhenius relationships with pressure and reciprocal temperature. Typically, a change in temperature of 100°C results in a relative change in the elements of diffusion matrix of 50 to 100%, whereas a change in pressure of 1 GPa introduces a relative change in elements of diffusion matrix of 4 to 6% for the haplobasalt, and less than 5% for the haplodacite. At a pressure of 1 GPa, the ratios between the major and minor eigenvalues of the diffusion matrix λ1/λ2 are not very sensitive to temperature variations, with an average of 5.5 +/- 0.2 for the haplobasalt and 3.7 +/- 0.6 for the haplodacite. The activation energies for the major and minor eigenvalues of the diffusion matrix are 215 +/- 12 and 240 +/- 21 kJ mol-1, respectively, for the haplodacite and 192 +/- 8 and 217 +/- 14 kJ mol-1 for the haplobasalt. These values are comparable to the activation energies for self-diffusion of calcium and silicon at the same melt compositions and pressure. At a fixed temperature of 1500°C, the ratios λ1/λ2 increase with the increase of pressure, with λ1/λ2 varying from 2.5 to 4.1 (0.5 to 1.3 GPa) for the haplodacite and 4 to 6.5 (0.5 to 2.0 GPa) for the haplobasalt. The activation volumes for the major and minor eigenvalues of the diffusion matrix are 0.31 +/- 0.44 and 2.3 +/- 0.8 cm3 mol-1, respectively, for the haplodacite and -1.48 +/- 0.18 and -0.42 +/- 0.24 cm3 mol-1 for the haplobasalt. These values are quite different from the activation volumes for self-diffusion of calcium and silicon at the same melt compositions and temperature. These differences in activation volumes between the two melts likely result from a difference in the structure and thermodynamic properties of the melt between the two compositions (e.g., partial molar volume).Applications of the measured diffusion matrices to quartz crystal dissolution in molten CAS reveal that the activation energy and activation volume for quartz dissolution are almost identical to the activation energy and activation volume for diffusion of the minor or slower eigencomponent of the diffusion matrix. This suggests that the diffusion rate of slow eigencomponent is the rate-limiting factor in isothermal crystal dissolution, a conclusion that is likely to be valid for crystal growth and dissolution in natural magmas when diffusion in liquid is the rate-limiting factor.